Analisis Sistem Informasi Akuntansi Penjualan Pada Apotek “ Z “ - Ovin Liviana Bela; Amin Sadiqin (CV ODIS, 2022)
The benefit of this research is that the author analyzes whether the sales accounting information system implemented at the